Jauja Matrix Church. Recovery plan and restorative intervention process - Cuadros Chávez, Hebner (2020)
Evaluation and diagnosis of the intervention proposal and the recovery process of the historical monument “Matriz Church” of the city of Jauja - Peru, carried out in 2009 and 2010. Comprehensive analysis of the project and the execution, regarding the methodological criteria and used, estimating its result and significance, as it is a heritage asset. Interpretation regarding the typology and methodology of the project and the restorative process, depending on the contextual scope of a political, social and cultural nature and in relation to the expectations, assessment and acceptance of the population on the cultural component, which projects a sense of collective identity and symbolizes the historical belonging of its inhabitants. Accuracies and evaluative comments on the project and the intervention and recovery procedures, taking stock of the respective criteria, achievements, shortcomings and disadvantages.